Problem Faced by The Public Due to The Improper Waste Disposal and Behaviour of Waste Disposal - Geetha, R.; Rajalakshmi, S. (International Journal of Social Sciences and Management, 2020)
The solid waste management is not only necessary for maintaining the hygienic environment but in reducing the probable health hazards. The current study deals with the problems faced by the public due to improper waste management and the behaviour in waste disposal. The data used in our study is both primary and the secondary data. Waste cannot be simply thrown away anymore, now it must be managed. Many materials thrown away could be saved by simple things like reusing glass, the municipal landfill could be reduced by almost 10 percent and there are still many advantages to waste management. Today, more people are in favour of companies who invest in “green products”. As a result, companies have removed phosphates, bleaches, and have made their paper products out of recycled papers. The objective of writing this paper is to study the current practices related to the various waste management initiatives taken in India for human wellbeing. The other purpose is to provide some suggestions and recommendations to improve the waste management practices in Indian towns. Int. J. Soc. Sc. Manage. Vol. 7, Issue-2: 70-77